2020
DOI: 10.1111/trf.15964
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of the properties of cold‐stored apheresis platelets suspended in PAS‐III with and without an 8‐hour room temperature hold

Abstract: Background: Use of extended cold storage of platelets promises to increase PLT availability and the bacterial safety of bleeding patients. No information is currently available on the preservation of apheresis PLT in vitro quality parameters when PLTs are held at room temperature early in the storage period prior to transfer to cold storage. Study Design and Methods: Double units of platelets suspended in 35% plasma/65% PAS-III were collected from normal consenting research donors and rested at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We conducted 12 different in vitro test for platelet components placed into cold storage 2 h post collection (control) compared to platelet components placed into the cold 8 h post collection (test) over 21 days of storage 22 . Eight matched pairs ( n = 8) were used for this evaluation, and the initial platelet yield for the split, paired units was 3.3 ± 0.3 × 10 11 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We conducted 12 different in vitro test for platelet components placed into cold storage 2 h post collection (control) compared to platelet components placed into the cold 8 h post collection (test) over 21 days of storage 22 . Eight matched pairs ( n = 8) were used for this evaluation, and the initial platelet yield for the split, paired units was 3.3 ± 0.3 × 10 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Detailed methods for the characterization study were previously reported in Wagner et al 22 The following in vitro parameters were evaluated: platelet count, pH (37°C), glucose (mM), lactate (mM), CD62P+ (p‐selectin, %), CD42b (GP1bA, MFI), Annexin V (%), CM‐H2DCFDA (ROS, MFI), and aggregation (with 4 different agonist experiments).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations